Silicon carbide ceramic slurry with high solid content and low viscosity as well as preparation method and application of silicon carbide ceramic slurry

Through the combination of aluminum salt-modified α-SiC powder with tetramethylammonium hydroxide, ethylene glycol and isopropanol, the preparation problem of high solid content and low viscosity slurry in the grouting molding of silicon carbide ceramic materials is solved, and high Molding of dense, high-strength silicon carbide ceramic components.

CN119161189AActive Publication Date: 2024-12-20SHANDONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411318619.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-20
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

During the grouting and forming process of silicon carbide ceramic materials, it is difficult to prepare slurries with high solid content and low viscosity, resulting in agglomeration and settlement of powders and affecting molding quality.

Method used

The dispersion and stability of the powder in water are improved by using aluminum salt-modified α-SiC powder and tetramethylammonium hydroxide, ethylene glycol and isopropanol as dispersants. Silicon carbide ceramic slurry with high solids content and low viscosity.

Benefits of technology

A high-solid content slurry with a viscosity of 0.2612Pa·s to 1.2402Pa·s was obtained, with good stability and fluidity, meeting the requirements of high solid content and low viscosity, ensuring high density and high silicon carbide ceramic components. strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052947510000071
    Figure BDA0005052947510000071
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic materials, in particular to high-solid-content and low-viscosity silicon carbide ceramic slurry as well as a preparation method and application thereof. The silicon carbide ceramic slurry comprises the following components: aluminum salt modified alpha-SiC powder and a dispersing agent, wherein the dispersing agent comprises tetramethylammonium hydroxide, ethylene glycol and isopropanol. The modified alpha-SiC powder is better in hydrophilicity, the zeta potential on the surface of the modified alpha-SiC powder is negative, tetramethylammonium hydroxide can be ionized in water, generated OH <-> provides a strong alkaline environment for a solution, the surface negative charge amount of the modified alpha-SiC powder is greatly increased, the Zeta negative potential on the surface is increased, and the surface performance of the modified alpha-SiC powder is improved. And agglomeration of the alpha-SiC powder is prevented. Meanwhile, hydroxyl groups in ethylene glycol and isopropanol molecules can form hydrogen bonds or Van der Waals force with the surface of the alpha-SiC powder so as to be adsorbed on the surfaces of particles, and steric hindrance is formed to prevent aggregation and precipitation of the powder. Therefore, the silicon carbide ceramic slurry with high solid content, low viscosity and stable performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a high-solid-content, low-viscosity silicon carbide ceramic slurry and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Silicon carbide ceramic material is a new type of high-temperature resistant ceramic with extremely strong covalent bonds. It has been widely used in the field of high-tech in recent years. It can be used as high-temperature furnaces, rocket combustion chamber linings, radar antenna covers, precision bearings, ceramic engines, nozzles, high-temperature turbine rotors, fuel devices, heat exchange components, nuclear reactor materials, etc.

[0004] The high reliability of silicon carbide materials is inseparable from its molding process. The molding process of silicon carbide ceramic materials is mainly divided into wet molding and dry molding. Dry molding includes dry pressing molding and isostatic pressing molding. Wet molding includes plastic forming type and colloidal molding. Colloidal molding mainly includes slip casting molding, tape casting and new colloidal molding methods.

[0005] Slip casting is a near-net-shape forming technology method with a relatively simple forming process, easy-to-control process, high efficiency, low cost, good uniformity of formed silicon carbide ceramic blanks, and can form complex geometric shapes, large sizes, porous tubular supports and thin-walled blanks. The slip casting forming process of silicon carbide ceramics is as follows: inject an appropriate amount of water-soluble ceramic powder organic suspension slurry with good dispersibility into the gypsum mold, use the capillary force of the small holes in the gypsum mold to absorb excess water in the slurry, solidify the slurry, and adhere to the inner wall of the gypsum mold. After a certain period of drying and shrinkage, the formed blank is gradually separated from the gypsum mold, and the blank is removed from the mold.

[0006] The success of grouting molding depends on the preparation of slurry, which requires high solid content (volume solid content ≥ 50%), low viscosity (≤ lPa·S), good fluidity, good stability, high uniformity, low thixotropy, and good permeability. Low viscosity facilitates smooth grouting, while high solid content ensures the acquisition of high-density and high-strength green blanks. However, there is a certain contradiction between high solid content and low viscosity. The high solid content powder will produce a certain amount of agglomeration and sedimentation. Therefore, how to prepare silicon carbide ceramic slurry with high solid content, low viscosity and stable performance has become an urgent problem to be solved in the field of silicon carbide ceramic parts production. Summary of the invention

[0007] In order to overcome the above problems, the present invention provides a high-solid content, low-viscosity silicon carbide ceramic slurry and a preparation method and application thereof.

[0008] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0009] The first aspect of the present invention provides a high solid content, low viscosity silicon carbide ceramic slurry, the components of the silicon carbide ceramic slurry include: aluminum salt modified α-SiC powder and a dispersant, wherein the dispersant includes tetramethylammonium hydroxide, ethylene glycol and isopropanol.

[0010] The second aspect of the present invention provides a method for preparing the silicon carbide ceramic slurry according to the first aspect, comprising:

[0011] Mixing tetramethylammonium hydroxide, ethylene glycol, isopropyl alcohol and deionized water to obtain a mixed dispersion;

[0012] The aluminum salt-modified α-SiC powder is added to the mixed dispersion in batches and stirred to obtain silicon carbide ceramic slurry.

[0013] The beneficial effects of the present invention are:

[0014] (1) In order to improve the dispersion stability of α-SiC powder in water, Al(NO3)3 is first used to modify it. The modified α-SiC powder has better hydrophilicity and the zeta potential on the surface of the modified α-SiC powder is negative. Tetramethylammonium hydroxide will ionize in water: The generated OH - Providing a strong alkaline environment for the solution greatly increases the amount of negative charge on the surface of the modified α-SiC powder, reduces the surface negative Zeta potential, and prevents the agglomeration of the α-SiC powder. At the same time, the ethylene glycol molecule contains two hydroxyl groups, and the isopropanol molecule contains one hydroxyl group. The hydroxyl group can form hydrogen bonds or van der Waals forces with the surface of the α-SiC powder to be adsorbed on the surface of the α-SiC particles, forming a steric hindrance to prevent the powder from agglomerating and precipitating. Therefore, the present invention can obtain a silicon carbide ceramic slurry with high solid content, low viscosity, and stable performance.

[0015] (2) The ceramic slurry prepared by the present invention has a viscosity of 0.2612 Pa·s to 1.2402 Pa·s at a solid content of 65 vol.%, and a sedimentation height of 1.5 mm to 4 mm after standing for 12 hours. It has good stability and meets the requirements of high solid content and low viscosity. DETAILED DESCRIPTION

[0016] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0017] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0018] A first typical embodiment of the present invention provides a high solid content, low viscosity silicon carbide ceramic slurry, the components of which include: aluminum salt-modified α-SiC powder and a dispersant, wherein the dispersant includes tetramethylammonium hydroxide, ethylene glycol and isopropyl alcohol.

[0019] In one or more embodiments, the mass ratio of the aluminum salt-modified α-SiC powder to tetramethylammonium hydroxide, ethylene glycol and isopropanol is 100:2:0 to 6.1:2.6, preferably 100:2:5.5:2.6.

[0020] In one or more embodiments, the preparation method of aluminum salt modified α-SiC powder includes: placing α-SiC powder and aluminum salt in deionized water, heating and stirring, and collecting solids to obtain aluminum salt modified α-SiC powder.

[0021] Preferably, the α-SiC powder includes α-SiC powders with particle sizes of 0.5 μm, 2.5 μm, and 10 μm, respectively.

[0022] More preferably, the mass ratio of α-SiC powder with a particle size of 0.5 μm, α-SiC powder with a particle size of 2.5 μm and α-SiC powder with a particle size of 10 μm is 2-7:2-8:1-7, preferably 5:8:7, 3:4:3, 7:8:5 and 2:2:1.

[0023] Preferably, the aluminum salt comprises Al(NO3)3.

[0024] Further preferably, the mass ratio of α-SiC powder to Al(NO3)3 is 1:0.002 to 0.008.

[0025] Preferably, the heating and stirring temperature is 50 to 80° C., and the heating and stirring time is 3 to 6 hours.

[0026] Preferably, the method for collecting the solid comprises centrifuging and removing the supernatant to obtain the aluminum salt-modified α-SiC powder.

[0027] More preferably, the centrifugal separation rate is 3500-4500 r / min, and the centrifugal separation time is 5-10 min.

[0028] Preferably, the solid is collected, dried, and then passed through a 80-100 mesh sieve to obtain aluminum salt-modified α-SiC powder.

[0029] A second typical embodiment of the present invention provides a method for preparing the silicon carbide ceramic slurry according to the first aspect, comprising:

[0030] Mixing tetramethylammonium hydroxide, ethylene glycol, isopropyl alcohol and deionized water to obtain a mixed dispersion;

[0031] The aluminum salt-modified α-SiC powder is added to the mixed dispersion in batches and stirred to obtain silicon carbide ceramic slurry.

[0032] In one or more embodiments, tetramethylammonium hydroxide, ethylene glycol, isopropanol and deionized water are stirred and mixed to obtain a mixed dispersion, wherein the stirring speed is 200 to 400 r / min and the stirring time is 10 to 15 min.

[0033] In one or more embodiments, the aluminum salt-modified α-SiC powder is added to the mixed dispersion in batches, and the stirring is performed to obtain the silicon carbide ceramic slurry at a stirring speed of 100 to 400 r / min and a stirring time of 16 to 24 h.

[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0035] Example 1

[0036] (1) Disperse 100 g of α-SiC powder with a particle size of 0.5 μm and 0.5 g of Al(NO3)3 powder in 200 mL of deionized water, stir in a water bath at 60°C, at a rate of 500 r / min, and for 5 h. Centrifuge the stirred α-SiC suspension in a high-speed centrifuge (4500 r / min, 10 min) to separate the supernatant, collect the solid, dry it in a forced air drying oven at 50-80°C, and sieve it through a 80-100 mesh sieve to obtain aluminum salt-modified α-SiC powder (0.5 μm).

[0037] (2) Disperse 100 g of α-SiC powder with a particle size of 2.5 μm and 0.5 g of Al(NO3)3 powder in 200 mL of deionized water, stir in a water bath at 60°C, at a rate of 500 r / min, and for 5 h. Centrifuge the stirred α-SiC suspension in a high-speed centrifuge (4500 r / min, 10 min) to separate the supernatant, collect the solid, dry it in a forced air drying oven at 50-80°C, and sieve it through a 80-100 mesh sieve to obtain aluminum salt-modified α-SiC powder (2.5 μm).

[0038] (3) Disperse 100 g of α-SiC powder with a particle size of 10 μm and 0.5 g of Al(NO3)3 powder in 200 mL of deionized water, stir in a water bath at 60°C, at a rate of 500 r / min, and for 5 h. Centrifuge the stirred α-SiC suspension in a high-speed centrifuge (4500 r / min, 10 min) to separate the supernatant, collect the solid, dry it in a forced air drying oven at 50-80°C, and sieve it through a 80-100 mesh sieve to obtain aluminum salt-modified α-SiC powder (10 μm).

[0039] Example 2

[0040] Add 2.4 g of 25% aqueous solution of tetramethylammonium hydroxide (the amount of water is 1.8 ml), 1.5 mL of ethylene glycol, 1 mL of isopropanol and 0.7 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 400 r / min, and stir for 15 min to obtain a mixed dispersion.

[0041] Example 3

[0042] The aluminum salt-modified α-SiC powder (0.5 μm), aluminum salt-modified α-SiC powder (2.5 μm) and aluminum salt-modified α-SiC powder (10 μm) prepared in Example 1 were weighed in a mass ratio of 5:8:7, and a total of 30 g was weighed. The three modified α-SiC powders were mixed evenly and added to the mixed dispersion configured in Example 2 in batches, with the added masses being 10 g, 5 g, 4 g, 3 g, 2 g, 2 g, and 2 g, respectively, and the remaining 2 g of powder was added in 10 times. The mechanical stirrer was operated continuously at a speed of 300 r / min. During the process of adding the salt-modified α-SiC powder in batches, the viscosity of the slurry needed to be monitored in real time, and the maximum solid content of the slurry at a viscosity less than 1.0 Pa·s was obtained. The slurry was continued to be stirred for 24 h.

[0043] In this embodiment, in theory, 30g of aluminum salt-modified α-SiC powder is dissolved in 5mL of the mixed dispersion in the above embodiment 2 to obtain a ceramic slurry with a solid content of 65vol.%, but in the actual addition process, as the mass of silicon carbide powder added increases, the state of the slurry changes and may even fail to form a slurry. Therefore, in order to maintain the stability of the slurry, a solvent such as deionized water, ethylene glycol or isopropanol and other organic dispersants are added to the slurry during the preparation of the slurry to maintain the slurry properties, but this will reduce the slurry solid content due to the increase in liquid volume. Therefore, in this embodiment, 30g of silicon carbide powder is completely added, and the amount of solvent is supplemented during the slurry preparation process. Finally, this embodiment can obtain a slurry with a solid content of 55-60vol.%, a slurry viscosity of 0.5779-1.2401Pa·s, and a silicon carbide slurry stability h / h0=4.902-5.387%. Stability refers to the ratio of the height h0 of the precipitated liquid to the original height h of the slurry after the slurry is left to stand for 24 hours.

[0044] During the pulping process of the slurry with a solid content of 55 vol.%, 2.5 mL of deionized water was added, and its viscosity was 0.5779 Pa·s and the stability was 4.902%; during the pulping process of the slurry with a solid content of 60 vol.%, 0.7 mL of ethylene glycol and 0.5 mL of isopropanol were added, and the corresponding viscosity was 1.2401 Pa·s; and the stability was 5.387%.

[0045] Solid content calculation formula:

[0046]

[0047] Example 4

[0048] The aluminum salt-modified α-SiC powder (0.5 μm), aluminum salt-modified α-SiC powder (2.5 μm) and aluminum salt-modified α-SiC powder (10 μm) prepared in Example 1 were weighed in a mass ratio of 3:4:3, and a total of 30 g was weighed. The three modified α-SiC powders were mixed evenly and added to the mixed dispersion configured in Example 2 in batches, with the added masses being 10 g, 5 g, 4 g, 3 g, 2 g, 2 g, and 2 g, respectively, and the remaining 2 g of powder was added in 10 times. The mechanical stirrer was operated continuously at a speed of 300 r / min. During the process of adding the salt-modified α-SiC powder in batches, the viscosity of the slurry needed to be monitored in real time, and the maximum solid content under which the viscosity of the slurry was less than 1.0 Pa·s was obtained (the powder was not completely exhausted during the addition process), and the slurry was continued to be stirred for 24 h.

[0049] In this embodiment, in theory, 30g of aluminum salt-modified α-SiC powder is dissolved in 5mL of the mixed dispersion in the above embodiment 2 to obtain a ceramic slurry with a solid content of 65vol.%, but in the actual addition process, as the mass of silicon carbide powder added increases, the state of the slurry changes and may even fail to form a slurry. Therefore, in order to maintain the stability of the slurry, a solvent such as deionized water, ethylene glycol or isopropanol and other organic dispersants are added to the slurry during the preparation of the slurry to maintain the slurry properties, but this will reduce the solid content of the slurry due to the increase in liquid volume. Therefore, in this embodiment, 30g of silicon carbide powder is completely added, and the amount of solvent is supplemented during the slurrying process. Finally, this embodiment can obtain a slurry with a solid content of 60-65vol.%, a slurry viscosity of 0.2612-0.3639Pa·s, and a silicon carbide slurry stability h / h0=4.525-5.321%.

[0050] The slurry with a solid content of 60 vol.% was supplemented with 0.5 mL of ethylene glycol and 0.5 mL of isopropanol during the slurry making process, and its viscosity was 0.2612 Pa·s and stability was 4.525%; the slurry with a solid content of 65 vol.% had a viscosity of 0.3639 Pa·s and stability of 5.321%.

[0051] Example 5

[0052] The aluminum salt-modified α-SiC powder (0.5 μm), aluminum salt-modified α-SiC powder (2.5 μm) and aluminum salt-modified α-SiC powder (10 μm) prepared in Example 1 were weighed in a mass ratio of 7:8:5, and a total of 30 g was weighed. The three modified α-SiC powders were mixed evenly and added to the mixed dispersion configured in Example 2 in batches, with the added masses being 10 g, 5 g, 4 g, 3 g, 2 g, 2 g, and 2 g, respectively, and the remaining 2 g of powder was added in 10 times. The mechanical stirrer was operated continuously at a speed of 300 r / min. During the process of adding the salt-modified α-SiC powder in batches, the viscosity of the slurry needed to be monitored in real time, and the maximum solid content under which the viscosity of the slurry was less than 1.0 Pa·s was obtained (the powder was not completely exhausted during the addition process), and the slurry was continued to be stirred for 24 h.

[0053] In this embodiment, in theory, 30g of aluminum salt-modified α-SiC powder is dissolved in 5mL of the mixed dispersion in the above embodiment 2 to obtain a ceramic slurry with a solid content of 65vol.%, but in the actual addition process, as the mass of silicon carbide powder added increases, the state of the slurry changes and may even fail to form a slurry. Therefore, in order to maintain the stability of the slurry, a solvent such as deionized water, ethylene glycol or isopropanol and other organic dispersants are added to the slurry during the preparation of the slurry to maintain the slurry properties, but this will reduce the slurry solid content due to the increase in liquid volume. Therefore, in this embodiment, 30g of silicon carbide powder is completely added, and the amount of solvent is supplemented during the slurrying process. Finally, this embodiment can obtain a slurry with a solid content of 55-59vol.%, a slurry viscosity of 0.3997-0.4625Pa·s, and a silicon carbide slurry stability h / h0=4.985-5.347%.

[0054] Among them, 1.5mL ethylene glycol and 1mL isopropanol were added to the slurry with a solid content of 55vol.% during the slurry making process, and its viscosity was 0.3997Pa·s and the stability was 4.985%; when 0.6mL ethylene glycol and 0.7mL isopropanol were added to the slurry with a solid content of 59vol.%, the corresponding viscosity was 0.4625Pa·s and the stability was 5.347%.

[0055] Example 6

[0056] The aluminum salt-modified α-SiC powder (0.5 μm), aluminum salt-modified α-SiC powder (2.5 μm) and aluminum salt-modified α-SiC powder (10 μm) prepared in Example 1 were weighed in a mass ratio of 2:2:1, and a total of 30 g was weighed. The three modified α-SiC powders were mixed evenly and added to the mixed dispersion configured in Example 2 in batches, with the added masses being 10 g, 5 g, 4 g, 3 g, 2 g, 2 g, and 2 g, respectively, and the remaining 2 g of powder was added in 10 times. The mechanical stirrer was operated continuously at a speed of 300 r / min. During the process of adding the salt-modified α-SiC powder in batches, the viscosity of the slurry needed to be monitored in real time, and the maximum solid content under which the viscosity of the slurry was less than 1.0 Pa·s was obtained (the powder was not completely exhausted during the addition process), and the slurry was continued to be stirred for 24 h.

[0057] In this embodiment, in theory, 30g of aluminum salt-modified α-SiC powder is dissolved in 5mL of the mixed dispersion in the above embodiment 2 to obtain a ceramic slurry with a solid content of 65vol.%, but in the actual addition process, as the mass of silicon carbide powder added increases, the state of the slurry changes and may even fail to form a slurry. Therefore, in order to maintain the stability of the slurry, a solvent such as deionized water, ethylene glycol or isopropanol and other organic dispersants are added to the slurry during the preparation of the slurry to maintain the slurry properties, but this will reduce the slurry solid content due to the increase in liquid volume. Therefore, in this embodiment, 30g of silicon carbide powder is completely added, and the amount of solvent is supplemented during the slurrying process. Finally, this embodiment can obtain a slurry with a solid content of 55-57vol.%, a slurry viscosity of 0.5672-0.5996Pa·s, and a silicon carbide slurry stability h / h0=5.160-5.421%.

[0058] Among them, 1.8mL ethylene glycol and 0.7mL isopropanol were added to the slurry with a solid content of 55vol.% during the slurry making process, and its viscosity was 0.5672Pa·s and the stability was 5.160%; when 1mL ethylene glycol and 1mL isopropanol were added to the slurry with a solid content of 57vol.%, the corresponding viscosity was 0.5596Pa·s and the stability was 5.421%.

[0059] Comparative Example 1

[0060] In this embodiment, the dispersants are tetramethylammonium hydroxide and ethylene glycol.

[0061] Add 2.4 g of 25% aqueous solution of tetramethylammonium hydroxide (1.8 mL of water), 1.5 mL of ethylene glycol and 2.7 mL of deionized water into a beaker, stir evenly with a mechanical stirrer, maintain a speed of 400 r / min, and stir for 15 min to obtain a mixed dispersion.

[0062] The slurry was prepared according to the conditions in Example 3, and a silicon carbide slurry with a solid content of 60 vol% was obtained. The slurry had poor fluidity and a viscosity of 5.34 Pa·s at a shear rate of 60 1 / s, which was greater than 1.0 Pa·s.

[0063] Comparative Example 2

[0064] In this embodiment, the dispersants are tetramethylammonium hydroxide and isopropyl alcohol.

[0065] 2.4 g of 25% aqueous solution of tetramethylammonium hydroxide (1.8 mL of water), 1 mL of isopropanol and 3.2 mL of deionized water were added to a beaker and stirred evenly with a mechanical stirrer at a speed of 400 r / min for 15 min to obtain a mixed dispersion.

[0066] The slurry was prepared according to the conditions in Example 3, and a silicon carbide slurry with a solid content of 60 vol% was barely obtained. The slurry had poor fluidity and high viscosity that was difficult to measure.

[0067] Comparative Example 3

[0068] In this embodiment, the dispersants are ethylene glycol and isopropyl alcohol.

[0069] 1.5 mL of ethylene glycol, 1 mL of isopropanol and 2.5 mL of deionized water were added into a beaker and stirred evenly with a mechanical stirrer. The speed was maintained at 400 r / min and the stirring time was 15 min to obtain a mixed dispersion.

[0070] The slurry was prepared according to the conditions in Example 3. However, it could not be formed into a slurry when the solid content was 43 vol.%. This was because there was no tetramethylammonium hydroxide to increase the Zeta potential on the surface of the silicon carbide powder, and the electrostatic repulsion between the silicon carbide powders was weakened, making it easier for the powders to agglomerate with each other and difficult to form a slurry.

[0071] Comparative Example 4

[0072] Change to another solvent.

[0073] The dispersant cannot be replaced with ethanol, butanone, n-butanol, toluene, or ethyl acetate.

[0074] Tetramethylammonium hydroxide is used as a dispersant. It hydrolyzes in the slurry to produce hydroxyl groups, providing a strong alkaline environment. Another hydrolysis product is adsorbed on the surface of silicon carbide particles to increase the thickness of the double electron layer, which reduces the Zeta potential of silicon carbide particles and improves the dispersibility of the slurry. At the same time, isopropanol and ethylene glycol can be adsorbed on the surface of silicon carbide particles through hydrogen bonds or van der Waals forces to form an adsorption layer to play a steric hindrance role, while other organic substances with different groups cannot be effectively adsorbed on the surface of silicon carbide particles to form steric hindrance.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high solid content, low viscosity silicon carbide ceramic slurry, characterized in that: The components of the silicon carbide ceramic slurry include: α-SiC powder modified by aluminum salt and a dispersant, wherein the dispersant includes tetramethylammonium hydroxide, ethylene glycol and isopropanol.

2. The silicon carbide ceramic slurry according to claim 1, characterized in that The mass ratio of the aluminum salt-modified α-SiC powder to tetramethylammonium hydroxide, ethylene glycol and isopropanol is 100:2:0 to 6.1:2.6, preferably 100:2:5.5:2.

6.

3. The silicon carbide ceramic slurry according to claim 1, characterized in that: The preparation method of aluminum salt modified α-SiC powder comprises: placing α-SiC powder and aluminum salt in deionized water, heating and stirring, and collecting solid to obtain aluminum salt modified α-SiC powder.

4. The silicon carbide ceramic slurry according to claim 3, characterized in that: The α-SiC powder includes α-SiC powders with particle sizes of 0.5 μm, 2.5 μm and 10 μm, respectively. Preferably, the mass ratio of the α-SiC powder with a particle size of 0.5 μm, the α-SiC powder with a particle size of 2.5 μm and the α-SiC powder with a particle size of 10 μm is 2 to 7:2 to 8:1 to 7, preferably 5:8:7, 3:4:3, 7:8:5 and 2:2:1; Alternatively, the aluminum salt includes Al(NO3)3, and preferably, the mass ratio of α-SiC powder to Al(NO3)3 is 1:0.002 to 0.

008.

5. The silicon carbide ceramic slurry according to claim 3, characterized in that: The heating and stirring temperature is 50-80°C, and the heating and stirring time is 3-6h.

6. The silicon carbide ceramic slurry according to claim 3, characterized in that: The method for collecting solids includes removing the supernatant by centrifugation to obtain aluminum salt-modified α-SiC powder; preferably, the centrifugal separation rate is 3500-4500 r / min, and the centrifugal separation time is 5-10 min.

7. The silicon carbide ceramic slurry according to claim 3, characterized in that: The solid is collected, dried, and passed through a 80-100 mesh sieve to obtain aluminum salt-modified α-SiC powder.

8. The method for preparing the silicon carbide ceramic slurry according to any one of claims 1 to 7, characterized in that: include: Mixing tetramethylammonium hydroxide, ethylene glycol, isopropyl alcohol and deionized water to obtain a mixed dispersion; The aluminum salt-modified α-SiC powder is added to the mixed dispersion in batches and stirred to obtain silicon carbide ceramic slurry.

9. The preparation method according to claim 8, characterized in that: Tetramethylammonium hydroxide, ethylene glycol, isopropanol and deionized water are stirred and mixed to obtain a mixed dispersion, wherein the stirring speed is 200-400 r / min and the stirring time is 10-15 min.

10. The preparation method according to claim 8, characterized in that: The aluminum salt-modified α-SiC powder is added to the mixed dispersion in batches, and the silicon carbide ceramic slurry is obtained by stirring at a speed of 100 to 400 r / min and a stirring time of 16 to 24 hours.

Citation Information

Patent Citations

  • Preparation method of low-viscosity high-solid-content water-based sizing for solid phase sintering silicon carbide ceramics wet molding process

    CN108249928A

  • Silicon carbide ceramic-based composite material slurry for direct-writing 3D printing and preparation method of silicon carbide ceramic-based composite material slurry

    CN115304389A

  • Preparation method of silicon carbide micro powder

    CN116854483A

  • Gel connection method of pressureless sintered silicon carbide

    CN117602947A

  • A SiC Slurry and Manufacturing method of the same

    KR1020170044485A